Antibacterial activity from leaf extracts of Mentha cordifolia Opiz. by ethanol extraction - ตั้งตระการพงษ์ รองเดช; ตั้งตระการพงษ์ จุลจิตร์ (KKU Science Journal, 2016)
This study intended to investigate the antibacterial activity of Mentha cordifolia Opiz. extract, which was extracted by ethanol, inhibiting Staphylococcus aureus, Streptococcus pyogenes, Streptococcus agalactiae, Salmonella Typhi, Escherichia coli and Klebsiella pneumoniae by the agar disc diffusion method. It was found that Mentha cordifolia Opiz. extract highly inhibited Salmonella Typhi more effectively than Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, Streptococcus agalactiae and Streptococcus pyogenes with a mean clear zone of 13.17±0.05, 12.50±0.05, 12.00±0.07, 11.67±0.06, 11.00±0.03 and 10.50±0.02 mm., respectively. These results were statistically significant difference at the confidence level of 95% (P<0.05 ). Mentha cordifolia Opiz. extract can give highly antibacterial activity because of the two major components of essential oil of this plant which are eugenol phenol and thymol. These two components are widely used to inhibit a great number of pathogenic bacteria. The results of this study also reveal the potential uses of the extracts of native medicinal plants in inhibiting pathogenic bacteria and can be developed for use as prevention for bacterial infections.